2016
DOI: 10.1039/c6lc00949b
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive thermometer using a vacuum-packed Si resonator in a microfluidic chip for the thermal measurement of single cells

Abstract: A highly sensitive thermometer system for a living cell is proposed, fabricated, and evaluated. The system possesses a resonant thermal sensor surrounded by vacuum in a microfluidic chip. The measurement principle relies on resonant frequency tracking of the resonator in temperature variations due to the heat from a sample cell; the heat is conducted from the sample cell in the microfluidic channel via a heat guide connecting the resonator to a sample stage. This configuration can reduce heat loss from the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…Conventional permanent magnets were used for levitation. The balance between the magnetic field from the magnets and the diamagnetism materials is shown in (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional permanent magnets were used for levitation. The balance between the magnetic field from the magnets and the diamagnetism materials is shown in (1).…”
Section: Methodsmentioning
confidence: 99%
“…In microfabricated temperature detection sensors or systems, thermal insulation should be carefully considered because heat loss depends on the surface-volume ratio. As thermal insulation methods, a suspended membrane under sensors and vacuumsurrounded structure is effective, and some papers have employed these methods [1,2]; however, heat will flow as long as there are contacts of two materials, which makes it difficult to obtain the true values of heat amount.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that the developed device is very useful in observing the thermal phenomenon of biological cells . Experimentally, the heat loss of the sensor can be evaluated from temperature measurements when the sample stage is heated using a laser (Fig.…”
Section: Applications Of the Cantilever Beam Temperature Sensormentioning
confidence: 98%
“…Considerable ongoing research has been devoted for the development of simple and cost-effective sensor systems for biological applications [1][2][3][4][5][6][7][8][9][10]. The detection of thermal activities of biological cells is of particular interest [11][12][13][14][15]. Measurement and temperature control of biological cells are considerable contributors to the development of new research methods in the study of genetics and the development of diseases, and they provide further insight into the behavior of cancerous tumors [16,17].…”
Section: Introductionmentioning
confidence: 99%